Studies on the Canacidae (Diptera), subfamily Apetaeninae. I. Apetaenus enderleini, nomen novum for Listriomastax litorea Enderlein, 1909, with remarks on the chaetotaxy, morphology, and habitats of the Apetaeninae from the Kerguelen Biogeographical Province - Munari, Lorenzo (Zootaxa, 2007)
A thorough examination of the chaetotaxy and morphology of the subantarctic Apetaeninae Apetaenus litoralis Eaton, 1875 and Listriomastax litorea Enderlein, 1909 has corroborated the early generic synonymy proposed by Hennig (1971). Thus, the latter genus is re-considered as a junior synonym of Apetaenus Eaton, 1875. Accordingly, Apetaenus litoreus (Enderlein, 1909), nomen preoccupatum by A. littoreus (Hutton, 1902), changes its specific epithet by designation of the new name Apetaenus enderleini [nomen novum]. New remarks and observations on the range of chaetotactic variation as well as on the female abdomen morphology are given. Further, distributional and ecological records from the literature are summarized. A key to the species of Apetaenus from the Kerguelen Biogeographical Province is also proposed. The presumed validity of Apetaenus watsoni Hardy, 1962 from Macquarie Island is briefly discussed.